2016
DOI: 10.1007/s11368-016-1485-3
|View full text |Cite
|
Sign up to set email alerts
|

Shifts of archaeal community structure in soil along an elevation gradient in a reservoir water level fluctuation zone

Abstract: Purpose Although archaea play an important role in nutrients cycling, the archaeal community in a reservoir water-level fluctuation zone (WLFZ) remains unclear. An elucidation of archaeal community responding to the environmental variables is essential to understand the nutrients dynamics in WLFZ. This study focused on the response of the archaeal community structure and abundance to the periodic water flooding along an elevation gradient in the WLFZ of the Three Gorges Reservoir. Materials and methods Along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…At a closer level, the dominant group Candidatus Nitrososphaera within Thaumarchaeota [ 68 ] increased its relative abundance with water addition. This observation was attributed to the increased plant growth, which could provide higher organic substrates for Candidatus Nitrososphaera [ 69 , 70 ]. This matched a previous study that found Candidatus Nitrososphaera performed better in organic-rich habitats [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…At a closer level, the dominant group Candidatus Nitrososphaera within Thaumarchaeota [ 68 ] increased its relative abundance with water addition. This observation was attributed to the increased plant growth, which could provide higher organic substrates for Candidatus Nitrososphaera [ 69 , 70 ]. This matched a previous study that found Candidatus Nitrososphaera performed better in organic-rich habitats [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…This method has been used worldwide to investigate the composition and distribution patterns of various soil microbial communities as well as their influencing factors [15][16][17][18]. However, this method has not been extensively used to study the rhizosphere microbial community composition in WLFZs [19]. Moreover, available high-throughput sequencing data have been primarily used to perform microbial community structure analyses (alpha and beta diversity) rather than functional studies.…”
Section: Introductionmentioning
confidence: 99%
“…Each qPCR reaction contained 10 μL SYBR ® Premix Ex Taq TM II (Takara, Japan), 0.8 μL of each primer (10 pmol μL –1 ), 1 μL DMSO, and 1 μL of template. qPCR assay was as follow: 95°C for 2 min, followed by 40 cycles of 95°C for 20 s, 63°C for 60 s, and 68°C for 60 s (Ye et al, 2016). The qPCR efficiencies were 84.0-92.1% ( R 2 > 0.990).…”
Section: Methodsmentioning
confidence: 99%